University Students’ Perceptions of Videotaping as a Teaching Tool in a Public Speaking Course - El Mortaji, Latifa (European Scientific Journal, ESJ, 2018)
The purpose of this study was to investigate the effect of videotaping on college students’ public speaking skills development in English as a Foreign Language (EFL) from the learners’ perspective. Twenty Moroccan freshmen students majoring in Engineering, Business, and Humanities at Al Akhawayn University in Ifrane, Morocco, participated in the study. Using 60 videotaped extemporaneous speeches, pre and post-videotaping surveys together with self-reflection essays, the researcher reports on students’ perceptions of and attitudes towards the effectiveness of videotaping on their public speaking competence development. Results revealed that the students’ public speaking skills improved over the course of a semester in terms of content, followed by non-verbal communication, verbal communication, organization, and language. In line with some previous research, this study confirms that a combination of videotaping and self-reflection has a major effect on improving students’ public speaking skills, developing confidence of EFL learners, and fostering independent learning